2013
DOI: 10.1089/jpm.2012.0393
|View full text |Cite
|
Sign up to set email alerts
|

Not Just Little Adults: Palliative Care Physician Attitudes Toward Pediatric Patients

Abstract: Palliative physicians tend to be willing to care for children, but perceive their level of training to be insufficient. Although additional training is endorsed, physicians favored real-time support and mentorship from a pediatric expert.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 15 publications
0
22
0
Order By: Relevance
“…34 Healthcare professionals reported having inadequate training, education or support to manage symptoms in children at end of life, and that they would value further training. [19][20][21]25,32,43,46,51,54,58,59,64,76 In one study, the barriers to obtaining the necessary education or training included a lack of opportunities, time and costs. 34 Fowler et al 36 found that healthcare professionals with formal training were more likely to feel comfortable treating pain and psychological issues.…”
Section: Barriers and Facilitators To Symptom Management Reported By mentioning
confidence: 99%
“…34 Healthcare professionals reported having inadequate training, education or support to manage symptoms in children at end of life, and that they would value further training. [19][20][21]25,32,43,46,51,54,58,59,64,76 In one study, the barriers to obtaining the necessary education or training included a lack of opportunities, time and costs. 34 Fowler et al 36 found that healthcare professionals with formal training were more likely to feel comfortable treating pain and psychological issues.…”
Section: Barriers and Facilitators To Symptom Management Reported By mentioning
confidence: 99%
“…In a survey of general palliative care providers, most described their pediatric training as inadequate, but they nonetheless provided palliative care for dying children. 19 Our study identified the theme of education across the priorities of decision making (Priority 3), care coordination (Priority 13), and symptom control (Priority 19). Quality palliative care training includes competencies in symptom assessment, pharmacologic and non-pharmacologic interventions, multidisciplinary team dynamics, decisional ethics, and communication skills.…”
Section: Discussionmentioning
confidence: 99%
“…In recent studies, physicians have reported a lack of comfort and confidence in providing pediatric palliative care, specifically as it pertains to psychosocial support. 57,58 PICU physicians reported that confidence and comfort increased as they practiced longer, but that the social and psychological needs of care remained areas that they did not feel as comfortable providing. 57 Palliative care physicians who provide support to pediatric patients indicated moderate to high levels of discomfort with ethical issues related to pediatric palliative care.…”
Section: Challenges To Providing High Quality Care To the Familymentioning
confidence: 99%
“…57 Palliative care physicians who provide support to pediatric patients indicated moderate to high levels of discomfort with ethical issues related to pediatric palliative care. 58 In general, physicians reported that their level of training was inadequate to prepare them for pediatric palliative care, especially as it relates to supporting families, talking with siblings, and participating in decision-making. 57,58 These findings highlight the importance of increased training and support for physicians in pediatric palliative care and interprofessional education.…”
Section: Challenges To Providing High Quality Care To the Familymentioning
confidence: 99%